Do fistula flow rate and fistula location have any effects on heart failure developing in patients with arteriovenous fistula? - Gündüz Yümün; Mehmet Okan Donbaloğlu; Selami Gürkan; Özcan Gür; Aykut Demirkıran (BMC Cardiovascular Disorders)
Abstract Background This study aims to explore the effects of arteriovenous fistula locations in the arm and fistula flow rates on the potential development of heart failure in patients with arteriovenous fistula (AVF). Material and methods A total of 116 patients with AVF due to chronic kidney disease were retrospectively reviewed between January 2022 and August 2022. Fifty-six patients with distal AVFs and 60 with proximal AVFs were compared in terms of demographic, clinical, and echocardiographic characteristics. Fistula flow rates were assessed using Doppler ultrasonography, while cardiac parameters were evaluated with echocardiography. The correlation between fistula location and cardiac parameters was analyzed using ROC analysis. Results The mean AVF blood flow rate was 1.47 (0.57–2.9) L/min for proximal fistulas and 0.85 (0.52–2.3) L/min for distal fistulas. There were statistically significant differences between the proximal and distal AVF groups regarding cardiac index, cardiac output, and cardiopulmonary recirculation values (p< 0.001). According to the New York Heart Association classification, Class III can be categorized as high cardiac output failure (HCOF), as cardiac index was calculated at 6.87 ± 1.65 L/min/m² (4.7–9.4), fistula flow rate at 2.60 L/min (2.1–2.9), and cardiac output at 8.08 ± 0.69 L/min. Conclusions When heart failure develops in patients with AVF, underlying heart disease should not be the sole factor considered. Proximal high-flow AVFs, in particular, may contribute to heart failure development and warrant careful monitoring.